2011
DOI: 10.1093/ije/dyr029
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes incidence and socio-economic position: a systematic review and meta-analysis

Abstract: The risk of getting type 2 diabetes was associated with low SEP in high-, middle- and low-income countries and overall. The strength of the associations was consistent in high-income countries, whereas there is a strong need for further investigation in middle- and low-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
605
11
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 785 publications
(698 citation statements)
references
References 63 publications
57
605
11
25
Order By: Relevance
“…Several studies reported abdominal obesity can be a risk factor for diabetes. [13,[15][16][17] In the present study, it was observed that the increasing in age was significantly associated with higher risk of impaired blood sugar and Type 2 diabetes [14,18,19] had reported the same results. This may be due to prolonged exposure to stress, obesity, genetic factor, and environmental risk factors with the advancement of age.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies reported abdominal obesity can be a risk factor for diabetes. [13,[15][16][17] In the present study, it was observed that the increasing in age was significantly associated with higher risk of impaired blood sugar and Type 2 diabetes [14,18,19] had reported the same results. This may be due to prolonged exposure to stress, obesity, genetic factor, and environmental risk factors with the advancement of age.…”
Section: Discussionsupporting
confidence: 55%
“…Dummy variables for age intervals are included to account for work experience as well as other effects of age on employment. Education is captured by dummy variables indicating if the highest level of schooling attained was either primary school, secondary school, high school, university or some other form of higher education with no education serving as the reference category, to control for the impact of education on employment and to account for the relationship between diabetes and education (Agardh et al, 2011). Since Mexico is a large and diverse country with regional socioeconomic differences as well as very poor rural and very developed urban areas, we also include regional dummies for five different Mexican regions 4 and three dummy variables to capture the effects of living in a rural or urban environment 5 , with rural as the reference category.…”
Section: Econometric Specificationmentioning
confidence: 99%
“…A systematic review and meta-analysis that was global in scope found associations with low levels of education (relative risk (RR) = 1.41, 95% CI: 1.28-1.51), with occupation (RR = 1.31, 95% CI: 1.09-1.57), and with low income (RR = 1.31, 95% CI: 1.09-1.57). While the data were limited from middle-and low-income countries in this study, the increased risks were independent of the income levels of countries (Agardh et al 2011). Another systematic review examining childhood socioeconomic status (SES) as a risk for T2DM found a strong relationship; although this relationship was attenuated by adult SES, a significant relationship remained (Tamayo et al 2010).…”
Section: Economic Statusmentioning
confidence: 68%